Could lexical and grammatical classes of late talkers predict the future children with SLI? - Benavides, Alejandra Auza; Murata, Chiharu (Revista de Investigación en Logopedia, 2021)
Today, it remains uncertain how to predict which children who are Late Talkers (LT) will be diagnosed in the near future as children with Specific Language Impairment (SLI). Little has been said about the classes of words they use, although they have been studied in depth through the Communication Development Inventories (CDI). The present study aims to expand on the information about the classes of words used by 15 LT between 18 and 30 months of age in two times of evaluation. The aim of the study is to differentiate a group of LT who are slower than the rest of LTs (called here Persistent LTs, according to the classes of words, the MLU and the grammatical complexity of sentences they produce and that are reported on the CDI. Results showed that it is possible to differentiate a group of HT from the classic LTs, through the classes of words they use, especially the use of verbs. The MLU and the grammatical complexity reported on the CDI were also useful for this goal. The different lexical and grammatical production patterns of LT subgroups in two different times of evaluation may provide guidelines for future work that seeks to bridge the gap between persistent late talkers and children with SLI.